DEVELOPMENT AND EVALUATION OF RITONAVIR MUCOADHESIVE MICROSPHERES - Velmurugan, Sellappan; Ashraf Ali, Mohamed (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of this research was to formulate and evaluate guar gum and ethyl cellulose mucoadhesive microspheres in combination with sodium alginate for controlled release of ritonavir. Materials and Methods: Microspheres were prepared by ionotropic gelation method using aluminum sulfate as a cross-linking agent. The developed ritonavir microspheres were characterized for micrometrics properties, morphology, drug entrapment efficiency, mucoadhesive property, in vitro drug release and interaction studies (Fourier transforms infrared spectroscopy [FTIR] and differential scanning calorimeter [DSC]). Results: The ritonavir mucoadhesive microspheres were free-flowing and discrete. The mean particle size ranged from 802.40±3.90 to 962.77±3.16 μm and the entrapment efficiencies ranged from 75.21 to 94.00%. All the ritonavir microsphere batches showed good in vitro mucoadhesive property ranging from 12 to 49% in the in-vitro wash off test. FTIR studies indicated the lack of ritonavir-polymer interactions in the ideal formulation F8. There were no compatibility issues and the crystallinity of ritonavir was found to be reduced in prepared mucoadhesive microspheres, which were confirmed by DSC and X-ray diffraction studies. Among different formulations, the ritonavir microspheres of batch F8 had shown the optimum percent drug entrapment of microspheres and the controlled release of the ritonavir for about 12 hrs. Release pattern of ritonavir from F8 microspheres batch followed Korsmeyers-Peppas and zero-order release kinetic model. The value of ‘n' was found to be 1.593, which indicates that the drug release was followed super Case-II transport type. Stability studies were carried out for F8 formulation at 4°C/ambient, 25±2°C/60±5%, 40±2°C/75±5% relative humidity revealed that the drug entrapment and mucoadhesive behavior were within permissible limits. Conclusion: The results obtained in this present work demonstrate the potential use of ethyl cellulose polymer for preparation of controlled delivery ritonavir mucoadhesive microspheres and prolonged residence at the absorption site. Keywords: Guar gum, Ethyl cellulose, Mucoadhesive microspheres, Ritonavir